Florasona: Where your voice becomes water, and the earth responds with life - Silva Abanto, Roger; Bustamante Acuña, Yaan; Correa Chugnas, Jhennyffer; Duran Cortez, Franclin; Gallardo Pastor, Ruth; Julón Mendoza, Tatiana (LACCEI, 2025)
Abstract– The present study entitled "Florasona: where your voice becomes water and the earth responds with life", had as an experimental setting its development in a school garden located in Annex Río Grande - Sector el Pedregal, La Encañada, which has as its general objective to propose an improvement model based on an automated irrigation system controlled by voice commands and ambient sounds, which optimizes water use in small-scale agricultural spaces, promoting sustainability and technological accessibility. Methodologically, this project has an applied approach, with technological design and experimental functional evaluation, developing a prototype that integrates soil moisture sensors, voice detection modules, automatic valves, Arduino-type microcontrollers and a continuous tracking App. Validation will be carried out through controlled tests in real or simulated contexts. Direct observation methods, water consumption records and user satisfaction surveys will be used. Tests conducted on horticultural plants revealed an average deviation of ±3% in moisture content and a 30% water saving. The results demonstrate the viability of "Florasona" as an efficient, sustainable, and easy-to-use solution for water management in small agricultural spaces.